The mystique of transmission : on an early Chan history and its contexts - Adamek, Wendi Leigh (Columbia University Press, 2007)
The Mystique of Transmission is a close reading of a late-eighth-century Chan/Zen Buddhist hagiographical work, the Lidai fabao ji (Record of the Dharma-Jewel Through the Generations), and is its first English translation. The text is the only remaining relic of the little-known Bao Tang Chan school of Sichuan, and combines a sectarian history of Buddhism and Chan in China with an account of the eighth-century Chan master Wuzhu in Sichuan. Chinese religions scholar Wendi Adamek compares the Lidai fabao ji with other sources from the fourth through.